GAMBARAN PERSALINAN PADA PROGRAM JAMPERSAL DI RSU PROF. DR. R. D KANDOU MANADO - Tondolambung, Priscillia; Tendean, Hermie; Kaeng, Juneke J. (e-Biomedik, 2013)
Abstract: Jampersal stand for financing service childbirth is covering to examine the pregnancy, birth aid, the parturition, including family planning service post delivery and newborn service performed by health professionals in health facilities. The purpose of this study was to know description of childbirth on Jampersal program at Prof. Dr. R. D Kandou. This research used retrospective descriptive methods. The sample in this study were all of the birthing mother who used Jampersal at Prof. Dr. R. D Kandou general hospital Manado from April to December 2011. This study has shown indicate that there are 2800 delivery cases was found using the Jampersal program from 3561 total of childbirth. Most childbirth which used Jampersal program is followed by multigravida (55,18%) at the age of 20 to 25 years (29,00%). Most woman came directly to the hospital (71,82%) and treated in hospital for more than 3 days (39,11%). Most labors using the Jampersal program were commonly aided spontaneously (66,93%). Conclusion: Description of childbirth on Jampersal program at Prof. Dr. R. D Kandou General Hospital most was followed by multigravida, at the age of 20-25 years, came directly to the hospital, treated for more than 3 days, and aided spontaneously. Keywords: Jampersal, Childbirth. Â  Â  Abstrak: Jampersal adalah jaminan pembiayaan pelayanan persalinan yang meliputi pemeriksaan kehamilan, pertolongan persalinan, pelayanan nifas termasuk pelayanan Keluarga Berencana (KB) paska persalinan dan pelayanan bayi baru lahir yang dilakukan oleh tenaga kesehatan di fasilitas kesehatan.Tujuan penelitian ini untuk mengetahui gambaran persalinan pada program Jampersal di RSU Prof. Dr. R. D Kandou. Penelitian ini menggunakan metode retrospektif deskriptif. Sampel penelitian yaitu semua ibu bersalin dengan program Jampersal di RSU Prof. Dr. R. D Kandou periode April - Desember 2011. Hasil penelitian menunjukkan bahwa terdapat 2800 kasus persalinan menggunakan program Jampersal dari 3561 total persalinan. Kebanyakan persalinan dengan menggunakan program Jampersal diikuti oleh ibu yang multigravida (55,18%) dengan usia 20-25 tahun (29,00%). Ibu yang bersalin paling banyak langsung datang sendiri ke rumah sakit (71,82%) dan kebanyakan dirawat di rumah sakit selama lebih dari 3 hari (39,11%). Persalinan menggunakan program Jampersal paling sering ditolong secara spontan (66,93%). Simpulan: Gambaran persalinan pada program Jampersal di RSU Prof. Dr. R. D Kandou kebanyakan diikuti oleh ibu yang multigravida, usia 20-25 tahun, langsung datang sendiri ke rumah sakit, dirawat selama lebih dari 3 hari dan ditolong secara spontan. Kata kunci: Jampersal, Persalinan.